Information systems management governance, urbanization and alignment - Alban, Daniel; Eynaud, Philippe; Malaurent, Julien; Richet, Jean-Loup 1988-; Vitari, Claudio (Wiley-ISTE, 2019)
Information Systems Management is intended to sensitize the heads of organizations to the issues raised by information systems (IS). Through its pedagogical presentation, the book ensures that issues related to IS are not left solely to the experts in the field. The book combines and analyzes three key concepts of IS: governance, urbanization and alignment. While governance requires the implementation of a number of means, bodies and procedures to manage IS more effectively, urbanization involves visualization methods to enable the manager to take into account the different levels of the organization of an IS and their coherence. Finally, alignment assesses the ability of the IS to make a significant contribution to the organization's strategy.